MEMENANGKAN BEASISWA DIKTI-FUNDED FULBRIGHT: TUJUH PETUNJUK PRAKTIS - Yustinus Calvin Gai Mali (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2022)
This article reports a community service activity that shares my practical tips specifically for lecturers and students about how to win a DIKTI-Funded Fulbright scholarship to study for a Ph.D. in the United States. This community service was conducted in one online synchronous session on Zoom on October 10, 2021. In the Zoom session, the author shared seven practical tips for the participants: (1) have supportive friends, (2) visit the American Indonesian Exchange Foundation (AMINEF) website, (3) review the scholarship requirements, (4) fill in the application form, now, (5) have some publications, (6) tell “real” contributions you can make, and (7) ask people to read and give feedback to your study objectives and personal statement. This article might interest those who are planning to apply for the same scholarship.